Inter-competitor outsourcing: On the advantages of profit and product launching time. (February 2022) - Yan, Yingchen; Zhao, Qiuhong; Qin, Zhongfeng; Lev, Benjamin
Abstract: Currently, an increasing number of firms have begun to outsource production to/from firms that compete in common markets. This work shows the dual roles of inter-competitor outsourcing: it can improve both firms' profits and alleviate conflicts between them in product launching time. Specifically, we establish an analytical model in which an original equipment manufacturer (OEM) and a contract manufacturer (CM) launch their respective products simultaneously or sequentially in the absence or presence of outsourcing. We incorporate the demand uncertainty of products and the demand information asymmetry between the firms, which may incentivize the less-informed firm to launch later to observe the other's production quantity and speculate the true demand. We employ a multistage Bayesian game to analyze the issue and obtain managerial insights. First, we find that the OEM's and CM's timing preferences both qualitatively change once outsourcing is introduced and that outsourcing renders firms more likely to achieve a consensus on launching time while they never do this under no outsourcing. This is because outsourcing not only alleviates fierce quantity competition, which leads to a lower total output and a better equilibrium price under a duopoly, but also suppresses the less-informed firm's benefit from the information acquired and the more-informed firm's loss from information leakage, which makes both parties amenable to the outcome. Moreover, in terms of profitability, we find that both firms can benefit from outsourcing compared with no outsourcing and the benefit that each firm earns increases as it delays the launch of its product. Highlights: We show the dual roles of intercompetitor outsourcing. We compare firms' optimal product launch timing without and with outsourcing. First, it can alleviate conflicts between the firms in product launch timing. Second, it can improve profits of competitive firms. The benefit firms earn from outsourcing increases with the delay of product launch.